2022
DOI: 10.55493/5008.v10i3.4552
|View full text |Cite
|
Sign up to set email alerts
|

Private Saving in Ghana: The Combined Efforts of Financial Development, Interest Rates, and Inflation

Abstract: Understanding private saving behavior of the citizenry is crucial for informed policy decisions in an economy. The reason is not far-fetched; economies gain sustained growth from investment through a positive saving culture. However, much of the available literature is on aggregate savings rather than on private saving behavior. This study looks at the combined effects of financial development, interest rates and inflation rates on private saving behavior among Ghanaians. Data for the study were obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…A group of studies have used legitimacy theory to examine disclosure practices green and social among companies (Deegan, 2013;Michelon et al, 2015;Pitrakkos and Maroun, 2020;Agbarha, 2022;Ahmad et al, 2022;Alnaa and Matey, 2022). It was emphasized that the support from the community was very much important for sustainability, survival, growth and corporate image.…”
Section: Theories Related To Green Accountingmentioning
confidence: 99%
“…A group of studies have used legitimacy theory to examine disclosure practices green and social among companies (Deegan, 2013;Michelon et al, 2015;Pitrakkos and Maroun, 2020;Agbarha, 2022;Ahmad et al, 2022;Alnaa and Matey, 2022). It was emphasized that the support from the community was very much important for sustainability, survival, growth and corporate image.…”
Section: Theories Related To Green Accountingmentioning
confidence: 99%
“…There is conflicting empirical evidence about the impact of financial education and information provided on saving literacy (Lusardi, 2004). Furthermore, even when studies show a considerable benefit of financial education on savings, the route behind this effect is frequently poorly understood (Anne Karani Iswan, Dr. Robert Arasa, 2020; Guellil and Benhabib, 2022;Hye, 2022;Alnaa and Matey, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Alternative energies have been widely studied in the literature as a means of improving environmental performance and mitigating the impacts of climate change. Researchers have consistently found that the increased usage of alternative energies can help to reduce CO 2 emissions (Adebayo and Kirikkaleli, 2021;Ayobamiji et al, 2022;Bamisile et al, 2021;Bekun, 2022;Charfeddine and Kahia, 2019;Ehigiamusoe and Dogan, 2022;Gielen et al, 2019;Haldar and Sethi, 2022;Qin et al, 2021;Hao et al, 2021;Hasnisah et al, 2019;Wang et al, 2020;Pata and Caglar, 2021;Sahoo and Sahoo, 2022;Sharif et al, 2020;Vo et al, 2020;Ali et al, 2021;Yuan et al, 2022;Zafar et al, 2019;Agbarha, 2022;Ahmad et al, 2022;Alnaa and Matey, 2022;Belesis et al, 2022;Faisal et al, 2022;Imasuen et al, 2022). Hao et al (2021), for example, found that the increased use of alternative energy sources can help to reduce emissions, which adds to air pollution and negative impacts on human health.…”
Section: Literature Reviewmentioning
confidence: 99%